Digital transformation and circular economy in universities (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to explore the relationship between digital transformation and circular economy practices in universities. A mixed-method approach was used to collect data from 500 participants comprising faculty, students, and staff of various universities in Peru. Data was collected using an online survey and analyzed using SPSS software. The findings of this study suggest that there is a positive relationship between digital transformation and circular economy practices in universities (r = 0.67,p 0.001). The regression analysis result showed that the level of digital transformation practices in universities significantly positively affected the adoption of circular economy practices (β = 0.61,p < 0.001). The study also highlights the importance of leadership support, stakeholder engagement, and resource availability in adopting circular economy practices. Based on the findings, the study recommends that universities prioritize adopting digital transformation practices and engage with a wide range of stakeholders to create a culture of sustainability. Future research should explore the role of leadership, stakeholder engagement, and resource availability in promoting circular economy practices in universities.